Home application alarm system with sms delivery notification - 449948 Tan, Cherng Yann (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Bachelor of Electrical (Electronics Engineering)) - Universiti Teknologi Malaysia, 2003